2015
DOI: 10.1007/s11307-015-0856-2
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Tracking of Streptococcal Infections of Subcutaneous Origin in a Murine Model

Abstract: Purpose Generation of plasmin in vivo by Streptococcus pyogenes is thought to localize the active protease complexes to the pathogen surface to aid in tissue dissemination. Here, we chose to follow cutaneous streptococcal infections by the use of non-invasive bioluminescence imaging to determine if this pathogen can be followed by this approach and the extent of bacterial spread in the absence of canonical plasminogen activation by streptokinase. Procedures Mice were injected subcutaneously with either biolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Our previous results indicated that the luminescence of Strep. Xen20 did not accurately reflect bacterial load in vivo and suggested this may be due to a D -glucose-mediated inhibitory effect (4). To confirm this finding on a static medium, we plated Strep .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous results indicated that the luminescence of Strep. Xen20 did not accurately reflect bacterial load in vivo and suggested this may be due to a D -glucose-mediated inhibitory effect (4). To confirm this finding on a static medium, we plated Strep .…”
Section: Resultsmentioning
confidence: 99%
“…Competition for carbon sources and energy may affect the survival of Streptococcus pyogenes ( S. pyogenes ) during an infection. Previously we found that a luxABCDE -incorporated S. pyogenes had reduced light production in D -glucose enriched medium (4). Although this trait is less desirable for Strep.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our previous results indicated that the luminescence of Strep. Xen20 did not accurately reflect bacterial load in vivo and suggested this may be due to a D -glucose-mediated inhibitory effect ( Davis et al, 2015 ). To confirm this finding on a static medium, we plated Strep .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we studied a luxABCDE -modified S. pyogenes Xen20 ( Strep . Xen20) to track the spread of cutaneous infection in wild-type mice ( Davis et al, 2015 ). By ex vivo colony forming units’ (CFUs) determination and Gram-staining histology, we noted live Streptococcus present in the distal organs of the infected animals.…”
Section: Introductionmentioning
confidence: 99%